(untitled) (Update Dental College Journal, 2025)
Background: Oral health is essential for physical well-being and has a significant influence on an individual’s quality of life. All age groups, including children, are prone to develop oral conditions due to a lack of information and awareness about oral health. Objectives: To explore the oral health practices and conditions of school-going children in the rural Sylhet. Materials and Methods: We conducted this cross-sectional study with a purposively selected group of 290 children attending Dhupagul Government Primary School in Sylhet, Bangladesh. From October 2023 to March 2024, we used a semi-structured questionnaire to interview the participants and performed oral examinations. Results: Most students brushed their teeth twice a day (56.6%), with 49.0% brushing before breakfast and 75.2% using toothpaste and brushes for cleaning. The mean DMFT score was 2.55±2.90. A statistically significant association was found between the total DMFT scores and the mean number of decayed teeth (p<0.05). Conclusion: The study identified that, while oral hygiene practices were good, and the overall oral health status was poor. Update Dent. Coll. j: 2025; 15(1): 1-5